Resistance and Synergism of Insecticides in Diamondback Moth, Plutella Xylostella (Lepidoptera : Yponomeutidae) - Moy, Kok Choy (2000)
A leaf-dipped bioassay was conducted to evaluate the toxicity of insecticides cypermethrin, permethrin, fipronil, avermectin b1 and emamectin benzoate against two lowland (Karak & Cheng strain) and a susceptible strains of diamondback moth (DBM). The synergistic effect of piperonyl butoxide (PBO), S,S,8- tributylphosphorotrithioate (DEF) and maleic acid diethyl ester (MADE) on the toxicity of the insecticides tested were also conducted by the combined leafdipped/topical bioassay. Both the lowland strains showed high LC50 values (> Ug/mL) for cypermethrin and permethrin. Based on the LC50 values, toxicities of the insecticides tested in decreasing order for the Karak and Cheng strains were : emamectin benzoate> avermectin b] > fipronil > permethrin > cypermethrin. The most toxic insecticide was emamectin benzoate with LC50 value of 1.62 X 10-5mg/L and 1.59 X 10-5mg/L for Cheng and Karak strain respectively. The slope of the concentration-mortality line indicated that both field-collected strains gave homogenous response towards the cypermethrin and permethrin but not the newer insecticides. The results also showed that the DBM developed high level of resistance toward cypermethrin and permethrin. Cheng strain showed a higher resistance ratio for fipronil compared with the Karak strain. In synergism study, cypermethrin was highly synergised by PBO compared to other insecticides tested. Cypermethrin was synergised 19.8-fold and 12.6-fold for Karak and Cheng strain respectively. Both DEF and MADE showed little synergistic effects to the insecticides tested with synergistic ratio of less than 3-fold for both Cheng and Karak strain respectively. The results suggested that microsomal monooxygenases played an important role in the detoxification metabolism of cypermethrin in both strains of DBM. Esterases and glutathione s-ttansferases, however, played a minor role in the metabolism of the insecticides for both strains of DBM.